Taxation problems of real estate in Ukraine - Bavrovska, N. (Land Management, Cadastre and Land Monitoring, 2017)
In this article studied the experience of Western countries concerning collection of property taxes and defines the peculiarities of foreign real estate taxation to improve the efficiency of collecting the aforementioned taxes in Ukraine taking into account the economic interests of the state and taxpayers. Defined problems of taxation of real estate in Ukraine and outlined prospects for their solution. Key words: foreign experience, property taxes, real estate object, tax rate, the tax base.